2001
DOI: 10.1037/0893-164x.15.3.268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking opportunity on attentional bias in smokers.

Abstract: The emotional Stroop task was used to examine the influence of opportunity to smoke on attentional bias to smoking-related stimuli. At the outset of the study, 92 nicotine-deprived smokers were told that they (a) would, (b) would not, or (c) might be able to smoke during the experiment. Next, participants completed an emotional Stroop task, in which they were presented with smoking-related or -unrelated words in an unblocked format. Smokers demonstrated interference to the smoking words, relative to matched ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 16 publications
7
78
0
Order By: Relevance
“…Thus, the ACC and DLPFC may act to make smoking cues more salient, an important factor in promoting drug use (Robinson and Berridge, 1993). Our study suggests that this attentional bias toward smoking cues is greater in the expectant state, which is consistent with previous behavioral studies (Wertz and Sayette, 2001).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the ACC and DLPFC may act to make smoking cues more salient, an important factor in promoting drug use (Robinson and Berridge, 1993). Our study suggests that this attentional bias toward smoking cues is greater in the expectant state, which is consistent with previous behavioral studies (Wertz and Sayette, 2001).…”
Section: Discussionsupporting
confidence: 91%
“…However, two factors that are believed to influence this neural response to drug cues, perceived drug availability and the user's level of abstinence, have seldom been investigated using functional brain imaging. Smokers report a greater urge to smoke when they are anticipating a cigarette (Droungas et al, 1995;Juliano and Brandon, 1998) or during nicotine withdrawal (Shiffman and Jarvik, 1976), and behavioral studies show that the cognitive and autonomic response to smoking cues can be affected by both abstinence (Gross et al, 1993;Johnsen et al, 1997) and expectancy to smoke (Carter and Tiffany, 2001;Wertz and Sayette, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Longer interference scores for emotion-laden words are interpreted as a preoccupation with the drugrelated stimuli. Increased interference time for drug-related words has been shown in subjects with dependence on cocaine (Copersino et al, 2004;Carpenter et al, 2006;Hester et al, 2006), alcohol (Bauer and Cox, 1998;Cox et al, 2002;Lusher et al, 2004), heroin (Franken et al, 2000), and nicotine (Gross et al, 1993;Wertz and Sayette, 2001;Waters et al, 2003). It has been proposed that this preoccupation with drug-related stimuli is a form of attentional bias thought to underlie relapse (Franken, 2003;Copersino et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Human drug addiction is a complex multifactorial phenomenon that features, with remarkable consistency, a difficulty in directing attention away from salient drug-related stimuli. Behavioral studies have shown that processing a nonsalient stimulus in the presence of a salient drug-related stimulus presents a significant difficulty for those dependent on cocaine (Copersino et al 2004;Hester et al 2006), alcohol (Sharma et al 2001;Ryan 2002;Cox et al 2003;Duka and Townshend 2004a, b), cannabis (Field et al 2004a), nicotine (Wertz and Sayette 2001;Powell et al 2002;Waters et al 2003;Bradley et al 2004;Field et al 2004b), or heroin (Lubman et al 2000;Franken et al 2003). Similarly, electrophysiological studies, which are able to directly quantify the allocation of processing resources to specific stimuli independently of conscious awareness, demonstrate enhanced event-related potential (ERP) responses to drugrelated stimuli compared to nonsalient stimuli across a range of addicted populations (Warren and McDonough 1999;Herrmann et al 2000Herrmann et al , 2001Franken et al 2003;van de Laar et al 2004;Lubman et al 2007b.…”
Section: Attentional Bias For Drug-related Stimulimentioning
confidence: 99%